Estimation of Ejection Fraction with Echocardiographic and Cardioangiographic Methods in 50 Cardiac Patients - B Soroor-Azimzadeh; S Shamsadini (Journal of Kerman University of Medical Sciences, 2003)
Ejection fraction is the most important indicator of heart failure. Angiography , is a standard method to demonstrate ejection fraction but it is invasive. Therefore determination of sensitivity and specificity of echocardiography versus angiography is a good guidance for physicians. A total number of 50 patients were enrolled in a prospective study. Two dimension and M-Mode echocardiography were first done in patients candidate for angiography and then they underwent coronary angiography. Sensitivity for M-Mode and 2D echocardiography was 59.4% and 43.8% and specificity for them was 100% and 94.4% respectively. The difference between the calculated amount of decrease in ejection fraction by 2D echo and angiography was statistically signifcant (p<o.ooo1) and for M-Mode echo and angiography was P=0.003. This means that with decreased ejection fraction,both echocardiography methods have less diagnostic accuracy in comparison to angiography. Pearson's correlation coefficient between calcuated ejection fractions by two modes of echocardiography and angiography was r=0.78 for M-Mode and r=0.44 for 2D which means a stronger correlation between M-mode echocardiography and angiography.